Conserved anti-inflammatory effects and sensing of butyrate in zebrafish. Issue 1 (9th November 2020) - Cholan, Pradeep Manuneedhi; Han, Alvin; Woodie, Brad R; Watchon, Maxinne; Kurz, Angela RM; Laird, Angela S; Britton, Warwick J; Ye, Lihua; Holmes, Zachary C; McCann, Jessica R; David, Lawrence A; Rawls, John F; et al.
ABSTRACT: Short-chain fatty acids (SCFAs) are produced by microbial fermentation of dietary fiber in the gut. Butyrate is a particularly important SCFA with anti-inflammatory properties and is generally present at lower levels in inflammatory diseases associated with gut microbiota dysbiosis in mammals. We aimed to determine if SCFAs are produced by the zebrafish microbiome and if SCFAs exert conserved effects on zebrafish immunity as an example of the non-mammalian vertebrate immune system. We demonstrate that bacterial communities from adult zebrafish intestines synthesize all three main SCFA in vitro, although SCFA were below our detectable limits in zebrafish intestines in vivo . Immersion in butyrate, but not acetate or propionate, reduced the recruitment of neutrophils and M1-type pro-inflammatory macrophages to wounds. We found conservation of butyrate sensing by neutrophils via orthologs of the hydroxycarboxylic acid receptor 1 ( hcar1 ) gene. Neutrophils from Hcar1-depleted embryos were no longer responsive to the anti-inflammatory effects of butyrate, while macrophage sensitivity to butyrate was independent of Hcar1. Our data demonstrate conservation of anti-inflammatory butyrate effects and identify the presence of a conserved molecular receptor in fish.